PENGARUH PEMBERDAYAAN USAHA KECIL DAN MENENGAH TERHADAP KESEJAHTERAAN MASYARAKAT DI KECAMATAN TOMPASO BARAT KABUPATEN MINAHASA - SERAN, ETNI DEBORA; Rorong, Arie Junus; Londa, Very (Sam Ratulangi University, 2017)
Improvement and empowerment of community resources in a planned and systematic way will greatlyaffect the improvement of people's welfare in Tompaso Barat District. This study uses quantitative research,which is trying to answer the magnitude of the effect of variables Empowering Small and MediumEnterprises to the Welfare Society.The data were collected with careful observation, including questionnaires in detailed contexts andin-depth interviews, as well as analysis results. Descriptive Statistics describes the mean and standarddeviation of the dependent and independent variables, the average public welfare being 31.87 means withthe standard deviation of 2,980. The average empowerment is 28.70 means with the standard deviation of2,902. Contribution of empowerment variable to welfare is obtained 48,0% it means that variation of societyprosperity change also influenced by variation of change of empowerment variable and the rest equal to52,0% which influenced by other factor. By empowering Small and Medium Enterprises in West TompasoSubdistrict will affect the welfare of the community as well as increase economic growth in each village.Keywords: Small and Medium Enterprise Empowerment, Public welfare